The role of interferons in pathogenesis of lupus erythematosus - Osmola, Agnieszka; Namysł, Jakub; Prokop, Janusz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
This paper reveal study results of interferon gamma and their receptor expression and serum concenrations in patients with various forms of lupus erythematosus. It also contains a short review of literature concerned with the role of interferons in lupus erythematosus pathogenesis.